Keefektivan Model Pembelajaran Project Based Learning dan Pemanfaatan Media Lingkungan dalam Meningkatkan Keterampilan Menulis Puisi Anak Pada Komunitas Harapan Kota Semarang - Agustina, Nadiya; Purnamasari, Iin; Mushafanah, Qoriati (CV. Supernova Office Stationary and Printing, 2023)
The background that drives this research is the lack of interest of children in writing rhymes. So that learning models and learning media are needed that are effective in improving rhymes writing skills. This type of research is quantitative research in the form of a Pre-Experimental Design with a One Group Pretest-Posttest design. The population of this study were phase C children in Harapan Community, Semarang City, with a total of 6 people. The results of the analysis of the results of the children's skill scores in writing poetry before being given treatment showed that three children got low scores (66.6%). Meanwhile, the scores of poetry writing skills after being given treatment showed that four children got high scores (66.6%), and two children who got very high scores (33.3%) with an average of 86.66. based on the t test analysis of two parties using (Paired Sample t-test), obtained a tcount of 19.057. With db = n1-1 = 6-1 = 5 and a significant level of 5% = 0.05, a ttable of 2.571 is obtained. So tcount > ttable = 19.057 > 2.571 so H0 is rejected and H1 is accepted. So it can be concluded that there is effectiveness in using the PjBL model and environmental utilization.